Beyond Discourse. Meaning in Lacanian Teachings - Savio, Karina (Káñina, 2023)
Considering the relevance that the notion of meaning presents for language studies, this article reviews the seminars and writings of Jacques Lacan with the aim of analyzing the ways in which the French psychoanalyst uses this term. We seek to review the different conceptualizations that are built around meaning to establish some points of dialogue with the approach with which discourse analysis operates. This work allows us to identify four time periods in which different theoretical frameworks are located around this category: 1953-1957, in which meaning is thought in relation to the formations of the unconscious; 1957-1964, in which it is articulated with the signifying chain and the Other; 1964-1974, in which it is differentiated from significance and characterized as a semblant, and, finally, 1974-1977, in which he is distinguished from the Real. These moments show certain continuities with respect to the elaborations that are interwoven, but also significant ruptures: while the reference to meaning as failed —by definition, all-meaning is never achieved— remains throughout the teachings, in the last years, a leak of meaning is located that refers to a beyond, anchored in the Real, which is outside the discourse.